THE INFLUENCE OF PERCEIVED PRODUCT’S QUALITY AND ELECTRONIC WORD OF MOUTH TOWARDS BRAND IMAGE AND PURCHASE INTENTION IN GENERATION Y (STUDY IN APPLE’S PRODUCT: IPHONE 7 AND IPHONE 7+) - admin, SHAHNAZ KHUMAIRA B12112018 (Jurnal Manajemen Update, 2017)
Abstract The largest segment of the population nowadays, are between the ages of 18 and 34, that are more educated and more culturally diverse than previous generations. These generation called Millenials or Generation Y will be the future buyers of the product that’s retailed, since the baby boomers and generation X are getting older, thus causing a great shift in spending power in our economy. It is important for the retailers to deliver the products, services, and messages that are relevant to the virtually and community-connected Generation Y. And so, the author is interested in examining such buying behaviour in the Generation Y by researching The Influence of Perceived Product’s Quality and Electronic Word of Mouth Towards Brand Image and Purchase Intention of Apple’s iPhone 7 and iPhone 7+ in Generation Y. The intention to purchase a product cause by so many factors, among those, Perceived Product’s Quality, Electronic Word of Mouth, and Brand Image are the cause of Purchase Intention that emerged on each individual. Brand Image also act as a mediating role. This research was carried out among the Generation Y that born in the 1980 – 1999, which is 17 to 34 years of age. The author used questionnaire as the main research instrument. SmartPLS 3.2.6 software used to complete the quantitative data. The result show that Perceived Product’s Quality and Electronic Word of Mouth had positively influence Brand Image and Purchase Intention of Apple’s iPhone 7 and iPhone 7+ in Generation Y. However Brand Image didn’t give any significant result toward the Purchase Intention of Apple’s iPhone 7 and iPhone 7+ in Generation Y.   Keyword: Perceived Product’s Quality, Electronic Word of Mouth, Brand Image,  Purchase Intention, Generation Y